Protection of Human Rights in the European Court of Human Rights - Alexander V. Fomichev; Tatiana V. Ekaterincheva (Евразийская интеграция: экономика, право, политика, 2019)
This research was aimed to study the legal basis of the organization and activities of the European Court of human rights, as well as the analysis of issues arising in the protection of human rights in the European Court of human rights. To this end, the categories of cases within the competence of the Court were identified, the analysis of the provisions of the European Convention on human rights and freedoms. The order of formation, structure and jurisdiction of the Court are investigated. Reveals the conditions for the submission of complaints referred from the applicant States or individuals. The problems of the admissibility of complaints.